Analisis Knowledge, Attitude dan Skill terhadap Competence pada penggunaan Media Pembelajaran E-Learning (Studi Evaluasi Model Pembelajaran Berbasis Simulator Polimarin Semarang) - Suyono Suyono; Warsina Warsina (Jurnal Maritim Polimarin, 2020)
E-learning is learning by utilizing information technology as a learning media, E-learning can be done by online or offline. Polimarin has a lot of information technology-based equipment that is used as a learning media to improve student or also called cadets competence. Many variables has affect the level of success of cadets in learning and achieving the competencies required by the seafarers' competency standards. In this analysis, the aim is to determine the influence of Knowledge, Attitude and Skill on the Competence of Polimarin cadets, especially the Nautics study program, so that both teachers and polimarin institutions can increase what variables have a strong influence on competence. The method used in this research is to use the quantitative approach method of multiple linear regression with SPSS-19 software as an analysis tool. The questionnaire was given to cadets for the 4th semester of the Nautics study program who will immediately carry out marine practice to assess the competence of cadets who have carried out learning in the Simulator. The results of this study, the knowledge variable has a significant influence on the competence of 0.274 or 27.7%, for the skill variable affects significantly by 0.350 or 35% on the competence of cadets, while the attitude variable has an influence of 0.113 or 11.3% on the variable competence. From this it can be concluded that the skill variable has the greatest influence on the competence of cadets, followed by the variable knowledge as the number two influence. And the last is the attitude variable that affects the competence of cadets in the Polimarin Nautical Study Program.